(untitled) (Annals of Medical Research, 2022)
Aim: We aimed to compare the effect on postoperative pain of pre-emptive bilateral Pectoral Nerve Block 2 by ultrasound with local anesthetic infiltration on the sternotomy line and drain insertion points in cardiac surgery. Materials and Methods: The study included 40 patients with open heart surgery under general anesthesia aged over 18 years. Patients were randomly divided into 2 groups. Group 1(bilateral Pectoral Nerve Block 2 (PECS 2) performed with ultrasound) and Group 2 (local anesthesia infiltration). Patients had intraoperative and postoperative opioid consumption amounts, duration on ventilator, visual analog scale (VAS) scores when moving (cough) and at rest, inspiratory flow rates and hospitalization duration recorded. Results: Group 1 was identified to have lower intraoperative and postoperative opioid consumption amounts (p<0.001). The rescue opioid requirements in the postoperative period were lower in Group 1 (p=0.002). The postoperative analgesia duration was longer in Group 1 (p=0.000). The duration on ventilator in the postoperative period was shorter for those with PECS 2 administration (p=0.010). The VAS score at rest was lower in Group 1 in the 48th hour (p=0.033). VAS score when moving was lower in Group 1 in the 24th and 48th hours (p=0.015, 0.001, respectively) After extubation, peak inspiratory flow rates were found to be statistically significantly higher in Group 1 in the 12th, 16th, 24th, 48th and 72nd hours. Conclusion: PECS 2 may be a part of Enhanced recovery after surgery protocols in cardiovascular surgery because of its contribution to lower VAS scores, less opioid consumption, and less pulmonary complications during the perioperative period.